Memórias, sonhos e símbolos de um processo de luto - Pacheco, Bernardete (2011)
The present study aimed to perform the reading of a symbolic mourning process in a dreamlike series and discuss the writing of the dreams as a resource to face the grief. The study was conducted through qualitative and documental analysis of a series of twenty three dreams that accompanied a grieving process over nearly eighteen years. The research gathered the theories of attachment, grief and analytical psychology a used strategies of dreams' analysis, in a more exploratory than interpretative way, viewing the understanding of the dynamics and symbolisms of the grief and its representation in dreams. The evidences pointed that the mourning dreams and their writing potentially constitute a facing resource of the symbolic grieving process